Strategi Pemasaran Digital dalam Meningkatkan Penjualan Produk Sepatu - At Thariq Harahap, Faqih; Irwan Padli Nasution, Muhammad (Teewan Journal Solutions, 2025)
The purpose of this study is to investigate efficient digital marketing techniques for boosting shoe product sales. In order to find and comprehend best practices in digital marketing, this research used a qualitative literature review technique to examine a variety of relevant material, including books, journal articles, and industry reports. The findings demonstrated that successful methods for contacting and interacting with customers included the use of social media, paid advertising, search engine optimization (SEO), and interactive content. While paid advertising aids in rapidly expanding market reach, social media is crucial for increasing brand recognition and engagement. Product exposure is increased via SEO, which facilitates brand discovery for customers. User-generated content (UGC) and user reviews are examples of interactive material that impacts purchasing choices and helps to establish trust. According to the study's findings, shoe product sales may rise significantly and sustainably when quantifiable and consistent digital marketing methods are used. The results provide businesses important information for creating and executing successful digital marketing plans.